Predicting students' attitudes toward and level of interracial interaction from interracial interaction expectation and campus racial climate. - Tamam, Ezhar
This study examines the influence of interracial interaction expectation and campus racial climate perception on attitudes toward interracial interaction, which, in tum, influences the level of interracial interaction among students. Responses from 193 Malay and 165 Chinese students were analyzed using hierarchical regression. Results support the hypothesized influence of interracial interaction expectation and campus racial climate perception on attitudes toward interracial interaction for the Chinese students. But for the Malay students only interracial interaction expectation is significant. Attitudes toward interracial interaction, in turn, significantly predict levels of interracial interaction for both groups. Implications for higher education are discussed.